Evaluasi Minat Baca Pelajar di Kota Metro - Fenny Thresia (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2014)
A city can be called developed when the population or community has a high interest with evident from the number of books published and the number of libraries in the country. It should be more and more publishing newspapers and magazines, it will impact on improving the reading of books. But unfortunately, this is only limited interest in reading improvement of people's interest in reading newspapers and magazines only. This evaluation is expected to generate inputs to increase student interest in reading at Kota Metro, considering our constitution also mandates the government and all of us to educate the nation. In addition, it can be used as consideration in policy- making related to the school library, city library, the park reading and other things related to the culture of reading in order to promote a culture of reading among students and the public.